2018
DOI: 10.1103/physrevb.97.104503
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced superconductivity in AgxBi2xSe3

Abstract: We investigated the pressure-dependence of electric transport and crystal structure of Ag-doped Bi 2 Se 3 . In the sample prepared by Ag-doping of Bi 2 Se 3 , the Bi atom was partially replaced by Ag, i.e., Ag 0.05 Bi 1.95 Se 3 . X-ray diffraction (XRD) patterns of Ag 0.05 Bi 1.95 Se 3 measured at 0 -30 GPa showed three different structural phases, with rhombohedral, monoclinic and tetragonal structures forming in turn as pressure increased, and structural phase transitions at 8.8 and 24 GPa. Ag 0.05 Bi 1.95 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…This result suggested that the β-FeSe 0.5 Te 0.5 sample had successfully been prepared. In addition, the energy dispersive x-ray spectroscopy data also indicated the stoichiometry of FeSe 0.51(2) Te 0.49 (2) for the prepared FeSe 0.5 Te 0.5 sample. We used this sample in the preparation of the (NH 3 ) y Li x FeSe 0.5 Te 0.5 that was used throughout this study.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…This result suggested that the β-FeSe 0.5 Te 0.5 sample had successfully been prepared. In addition, the energy dispersive x-ray spectroscopy data also indicated the stoichiometry of FeSe 0.51(2) Te 0.49 (2) for the prepared FeSe 0.5 Te 0.5 sample. We used this sample in the preparation of the (NH 3 ) y Li x FeSe 0.5 Te 0.5 that was used throughout this study.…”
Section: Resultsmentioning
confidence: 77%
“…Recently, the pressure dependence of superconductivity in metal-doped two-dimensional (2D) layered materials has attracted much attention [1][2][3][4][5][6][7][8][9][10][11] because of the expectation that a new superconducting pairing mechanism will be developed, as well as the emergence of new superconducting phases exhibiting higher superconducting transition temperatures (T c 's) than those observed at ambient pressure. The pressure-driven high-T c phase has been extensively investigated in metal-doped FeSe [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…X‐ray fluorescence holography (XFH) is a powerful tool for investigating the local atomic configuration around a selected element emitting fluorescent X‐rays . In particular, XFH has been performed for investigating local arrangements around dopants in various materials, such as Mn‐doped Bi 2 Te 3 topological insulator and Co‐doped TiO 2 magnetic thin film, which served to obtain an atomic‐level understanding on the role of dopants.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, ARH directly shows us the 3D local atomic structures which exist only around the selected dopants in a larger area. Photoelectron and X‐ray fluorescence ARH have already been practicalised and have provided rich information on the anomalies of atomic structures in various exotic materials, such as dilute magnetic semiconductors, relaxor ferroelectric materials, topological insulators and so on, which can never be obtained by other probes . The technical details and principles of X‐ray fluorescence ARH can be found in review papers …”
Section: Introductionmentioning
confidence: 99%